A systematic review of food waste audit methods in hospital foodservices: development of a consensus pathway food waste audit tool. Issue 1 (4th July 2021) - Cook, Nathan; Collins, Jorja; Goodwin, Denise; Porter, Judi
Abstract: Background: To understand, monitor and compare the scope of food waste in hospital foodservices, it is essential to measure food waste using a standardised method. The aims of this systematic review were to: (i) describe and critique the methodological features of waste audits used in hospital foodservice settings that measure aggregate food and food‐related waste and (ii) develop a consensus tool for conducting a food waste audit in a hospital foodservice setting. Methods: Seven electronic databases were searched for peer reviewed literature, and 17 Google Advanced searches located grey literature that described food waste audit methods previously used or developed for hospital foodservices. Study selection and quality assessment occurred in duplicate. Data describing the audit method, its feasibility, and strengths and limitations were extracted and synthesised to develop a consensus tool. Results: Eight peer reviewed and nine grey literature documents describing a variety of food waste audit methods were found. The most common practices were 2‐week data collection ( n  = 5), foodservice staff collecting data ( n  = 6), measuring food waste only ( n  = 11), measuring food waste at main meals ( n  = 5) and using electronic scales to measure waste ( n  = 12). A consensus tool was developed that proposes a method for preparing, conducting and analysing data from a food waste audit. Conclusions: This review used published evidence to develop the first ever food waste audit consensus tool for hospital foodservices to use and measure food and food‐related waste. Future research is needed to apply and test this tool in practice. Abstract : This systematic review of published and grey literature located 17 documents describing audit methods to aggregately measure hospital food and food‐related waste. The most common methods reported were: data collection for two weeks (n=5); foodservice staff collecting data (n=6); measuring food waste only (n=11); measuring food waste at all main meals (n=5); and using electronic scales to measure waste (n=12). Review findings have been synthesised into a consensus tool describing a method to conduct a food and food‐related waste audit in a hospital foodservice setting.